2018
DOI: 10.1093/ijnp/pyy024
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Treatment-Resistant Depression: A Critical Review and Future Perspectives

Abstract: Genetic biomarkers to identify patients with higher risk of treatment-resistant depression or to guide treatment in these patients are not available yet. Methodological improvements of future studies could lead to the identification of genetic biomarkers with clinical validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 78 publications
2
38
0
Order By: Relevance
“…Possible ways by which this could be achieved include: (1) identifying genetic predictors of non-response to specific antidepressant classes; (2) prescribing treatments with increased efficacy but limited availability because of costs constraints to patients having genetic risk for TRD. However, most existing pharmacogenomic studies were focused on measures of response to the last treatment without taking into account previous treatments, leaving the genetics of TRD largely unexplored 7 . Another issue was the investigation of common variants only, while the possible role of rare variants was overlooked, despite they were suggested as one of the factors contributing to missing heritability of common traits 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Possible ways by which this could be achieved include: (1) identifying genetic predictors of non-response to specific antidepressant classes; (2) prescribing treatments with increased efficacy but limited availability because of costs constraints to patients having genetic risk for TRD. However, most existing pharmacogenomic studies were focused on measures of response to the last treatment without taking into account previous treatments, leaving the genetics of TRD largely unexplored 7 . Another issue was the investigation of common variants only, while the possible role of rare variants was overlooked, despite they were suggested as one of the factors contributing to missing heritability of common traits 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Arguably, it is possible that genetic mechanisms could partly contribute to the emergence of tolerance to antidepressants in specific subsets of patients.The genetics of molecules putatively implicated in treatment loss of response or treatment-resistant depression included BDNF, GRIK4, KCNK2, SLC6A4, however, most studies have been based on candidate gene approach, and only for few genes replication supported associations with treatmentresistant depression. Among serotonin receptor, the GG variant for the rs7333412 SNP of the 5HT2A has shown association with less proneness to antidepressant response compared to the AA/AG variant.In the preclinical study, it has been demonstrated that the 5-HT2A receptors may have an inhibitory effect on the neuronal activity of the serotonergic neurons after acute administration of SSRIs GWAS (Genome-Wide Association Studies) did not detect any genome-wide significant association at the variant level, however, signal transduction including genes regulating synaptic plasticity, cytoskeleton architecture, and neurogenesis could be associated with treatment-resistant depression, according to the results by genome-wide association studies of antidepressant response[68].…”
mentioning
confidence: 99%
“…29,30 Enrichment was also identified in gene sets involved in cytoskeleton regulation and regulation of second messenger cascades, in line with previous findings. 4 Another encouraging finding was the observation of a significant higher expression of the genes of interest in some brain regions compared with other tissues (supplementary Figure 4).…”
Section: Key Findings and Interpretationmentioning
confidence: 79%
“…4 Another GWAS investigated the role of rare variants in TRD and again the most interesting results were obtained at the gene-set level, showing enrichment of rare variants in genes regulating actin cytoskeleton, although the finding did not survive multiple-testing correction. 4 The present paper reports a GWAS of common variants and a meta-analysis at the polymorphism, gene and gene-set (pathway) level, with the aim of contributing to filling the gap in our knowledge about TRD genetics.…”
Section: Resultsmentioning
confidence: 99%